Nuclear calcium sensors reveal that repetition of trains of synaptic stimuli boosts nuclear calcium signaling in CA1 pyramidal neurons - Bengtson, C. Peter; Freitag, H. Eckehard; Weislogel, Jan-Marek; Bading, Hilmar (Biophysical journal, 2010)
Nuclear calcium is a key signal in the dialogue between synapse and nucleus that controls the genomic responses required for persistent adaptations, including memory and acquired neuroprotection. The amplitude and duration of nuclear calcium transients specify activity-induced transcriptional changes. However, the precise relationship between synaptic input and nuclear calcium output is unknown. Here, we used stereotaxic delivery to the rat brain of recombinant adeno-associated viruses encoding nuclear-targeted calcium sensors to assess nuclear calcium transients in CA1 pyramidal neurons after stimulation of the Schaffer collaterals. We show that in acute hippocampal slices, a burst of synaptic activity elicits a nuclear calcium signal with a regenerative component at above-threshold stimulation intensities. Using classical stimulation paradigms (i.e., high-frequency stimulation (HFS) and θ burst stimulation (TBS)) to induce early LTP (E-LTP) and transcription-dependent late LTP (L-LTP), we found that the magnitude of nuclear calcium signals and the number of action potentials activated by synaptic stimulation trains are greatly amplified by their repetition. Nuclear calcium signals and action potential generation were reduced by blockade of either NMDA receptors or L-type voltage-gated calcium channels, but not by procedures that lead to internal calcium store depletion or by blockade of metabotropic glutamate receptors. These findings identify a repetition-induced switch in nuclear calcium signaling that correlates with the transition from E-LTP to L-LTP, and may explain why the transcription-dependent phase of L-LTP is not induced by a single HFS or TBS but requires repeated trains of activity. Recombinant, nuclear-targeted indicators may prove useful for further analysis of nuclear calcium signaling in vivo.
Gesehen am 16.01.2023